Overview of Policies for the Generation from Renewable Energy Focused in Central Tower Concentrating Solar Power - PabÃ³n LeÃ³n, Jhon A.; GarcÃa Mendoza, JosÃ© O.; Abril, Sofia Orjuela (International Journal of Energy Economics and Policy, 2020)
Nowadays, it does exist a general awareness about climatic change and its implications for the environment across the world. The Paris agreement (2015) agreed that greenhouse gas emissions should be reduced to 0%. For this reason, many countries are in search of innovation, development, and application of energy generation systems from renewable resources (solar, geothermal, hydraulic, wind), which are capable of covering the great trail that fossil fuels (oil) leave. Colombia has committed to achieving a reduction of 20% in the emission of greenhouse gases by 2030. To accomplish this common worldwide objective, the governments of the different countries have established energy policies and incentives that allow the transition of the economy based on fossil fuels to clean energy. Countries such as the USA, Mexico, Spain, Japan, Australia, and Germany have implemented solar plants (CSP) coupled with thermodynamic cycles such as the supercritical Brayton, where the working fluid is in supercritical conditions. Colombia does not possess a great development in this sector even though it has a huge potential, especially the north part of the country, for the implementation of solar energy. Just as some countries, so too, Colombia can improve its economy through the use of renewable energies if it implements more supporting policies. There are already studies and researches that insists on the previous statement. One of those, which includes the simulation of a solar plant, estimated that a plant in Barranquilla could supply about 50% of the demand with an approximate LCOE of 9.76 cents/KWh. This work shows the different national and international policies, measures, regulations, projects, and laws taken to encourage this change as well as to show the energy potential that has the solar power concentrating solar power (CSP) as an option to diversify the energy matrix of Colombia. Keywords: Alternative Fuels, Environmental Pollution, Energy Policy, Renewable Energy, Supercritical Brayton. JEL Classifications: L78, L90, O31, Q20 DOI: https://doi.org/10.32479/ijeep.9820